Validasi Proses Produksi Dektrosa Monohidrat (DMH) Farmasi pada Skala Pilot - Sri Mulyani Suharno; Didik Sudarsono; Eriawan Rismana; Indrawati Dian Utami; Lely Khojayanti; Bambang Srijanto; Ayustian Futu Wijaya (Media Penelitian dan Pengembangan Kesehatan, 2020)
Armaceutical dextrose monohydrate (DMH) as one of the raw materials for drugs which is widely used in the manufacture of infusions and drug preparations, including BBO, which is entirely still imported. To achieve the independence of national pharmaceutical raw materials, it is important to study and develop the DMH pharmaceutical production process technology in Indonesia. In this research, the validation of the DMH pharmaceutical production process using food quality liquid glucose raw materials on a pilot-scale of 5 - 6 kg/product was carried out. The validation process has been carried out three times in all stages of the process, namely saccharification, carbon purification, resin purification, evaporation, crystallization, centrifugation, and drying. Several test parameters have been established at each stage of the process so that the repeatability of the production process and the quality of pharmaceutical DMH can be achieved. The results showed that each stage of the process played a role in improving the quality of dextrose. Product yield and weight loss of dextrose in the whole process were 50–52% and 9–10%, respectively. The results of testing the levels of dextrose (dextrose equivalent/DE), endotoxin content, pyrogen-free tests, and other parameters that have been carried out on pharmaceutical DMH products have met the quality requirements according to the Indonesian Pharmacopoeia Edition V. In conclusion, the validation results show that the bench-scale pharmaceutical DMH production process technology is developed to produce pharmaceutical DMH products with process repeatability and good quality. Abstrak Dekstrosa Monohidrat (DMH) farmasi merupakan bahan baku obat (BBO) yang banyak digunakan pada pembuatan infus dan sediaan obat serta termasuk salah satu BBO yang seluruhnya masih dimpor. Untuk mencapai kemandirian bahan baku farmasi nasional, maka pengkajian dan pengembangan teknologi proses produksi DMH farmasi menjadi penting untuk dilakukan di Indonesia. Dalam penelitian ini telah dilakukan validasi proses produksi DMH farmasi menggunakan bahan baku glukosa cair kualitas pangan pada skala pilot 5–6 kg produk/bets. Proses validasi telah dilakukan sebanyak tiga kali ulangan pada seluruh tahapan proses yaitu sakarifikasi, pemurnian dengan karbon, pemurnian dengan resin, evaporasi, kristalisasi, sentrifugasi, dan pengeringan. Beberapa parameter uji telah ditetapkan pada setiap tahapan proses agar keterulangan proses produksi dan kualitas DMH farmasi dapat tercapai. Hasil penelitian menunjukkan bahwa setiap tahapan proses berperan dalam peningkatan kualitas dekstrosa. Rendemen produk dan kehilangan berat dekstrosa pada keseluruhan proses masing-masing adalah 50–52% dan 9–10%. Hasil pengujian kadar dekstrosa (dekstrosa ekivalen/DE), kandungan endotoksin, uji bebas pirogen, dan parameter lain yang telah dilakukan terhadap produk DMH farmasi adalah sudah memenuhi persyaratan kualitas sesuai Farmakope Indonesia Edisi VI. Disimpulkan, hasil validasi menunjukkan bahwa teknologi proses produksi DMH farmasi skala pilot yang dikembangkan dapat menghasilkan produk DMH farmasi dengan keterulangan proses dan kualitas yang baik.